Calculation of the time resolution of the J-PET tomograph using kernel density estimation. (26th May 2017) - Raczyński, L; Wiślicki, W; Krzemień, W; Kowalski, P; Alfs, D; Bednarski, T; Białas, P; Curceanu, C; Czerwiński, E; Dulski, K; Gajos, A; Głowacz, B; et al.
Abstract: In this paper we estimate the time resolution of the J-PET scanner built from plastic scintillators. We incorporate the method of signal processing using the Tikhonov regularization framework and the kernel density estimation method. We obtain simple, closed-form analytical formulae for time resolution. The proposed method is validated using signals registered by means of the single detection unit of the J-PET tomograph built from a 30 cm long plastic scintillator strip. It is shown that the experimental and theoretical results obtained for the J-PET scanner equipped with vacuum tube photomultipliers are consistent.